The Pharyngostomy Tube: Indications, Technique, Efficacy, and Safety in Modern Surgical Practice - Garza-Castillon, Rafael, Jr.; Berger, Jonathan; Andrade, Rafael; Podgaetz, Eitan (The Thoracic and Cardiovascular Surgeon, 2018)
Background Long-term nasogastric tubes are uncomfortable and associated with complications such as impairment with speech and swallowing, septum trauma, epistaxis, alar necrosis, and intubation of the trachea among others. Pharyngostomy tubes (PTs) are an alternative for prolonged enteral feeding, transluminal drainage of collections, and gastric decompression in patients with an intestinal obstruction and an inoperable abdomen.Patients and Methods This is a retrospective analysis of patients who had a PT placed at our institution from May 2005 to March 2015. The primary end point of the study was to establish the type and rate of complications and aspiration events related to PT use.Results During the specified period, a total of 84 PTs were placed. The most common indication for PT placement was enteric decompression in 65 (77.4%), followed by transluminal collection drainage in 12 (14.3%), and enteral access for nutrition in 7 (8.3%) patients. The mean time to tube removal was 17.8 days ± 17.1 (range, 2–119). We encountered 10 (11.2%) complications related to PT placement, including 7 cases of cellulitis, 2 superficial abscesses, and 1 patient with pharyngeal hemorrhage.Conclusion PTs are a relatively simple, safe, and straightforward approach to achieve long-term enteral decompression, access for feeding or transluminal drainage, avoiding the complications associated with prolonged nasogastric tube placement. The complication rate is low and patient satisfaction and compliance appear to be higher than with nasogastric tubes. Modern surgeons should be familiar with the procedure and technique. PTs should be part of every surgeon's armamentarium.
Keywords: esophageal; surgery/incisions; minimally invasive